Safe birth in cultural safety in southern Mexico: a pragmatic non-inferiority cluster-randomised controlled trial - Iván Sarmiento; Sergio Paredes-Solís; Abraham de Jesús García; Nadia Maciel Paulino; Felipe René Serrano de los Santos; José Legorreta-Soberanis; Germán Zuluaga; Anne Cockcroft; Neil Andersson (BMC, 2022)
Plain English summary In many Indigenous communities, traditional midwives support mothers during pregnancy, childbirth, and some days afterwards. Research involving traditional midwives has focused on training them in Western techniques and redefining their role to support Western care. In Guerrero state, Mexico, Indigenous mothers continue to trust traditional midwives. Almost half of these mothers still prefer traditional childbirths, at home, in the company of their families and following traditional practices. We worked with 30 traditional midwives to see if supporting their practice allowed traditional childbirth without worsening mothers' health. Each traditional midwife received an inexpensive stipend, a scholarship for an apprentice and support from an intercultural broker. The official health personnel participated in a workshop to improve their attitudes towards traditional midwives. We compared 40 communities in two municipalities that received support for traditional midwifery with 40 communities in two municipalities that continued to receive usual services. We interviewed 872 women with childbirth between 2016 and 2017. Mothers in intervention communities suffered fewer complications during childbirth and had fewer complications or deaths of their babies. They had more traditional childbirths and fewer perineal tears or infections across home-based childbirths. Among those who went to Western care, mothers in intervention communities had more traditional management of the placenta but more non-traditional cold-water baths. Supporting traditional midwifery increased traditional childbirth without worsening health outcomes. The small size of participating populations limited our confidence about the size of this difference. Health authorities could promote better health outcomes if they worked with traditional midwives instead of replacing them.